(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
Language development in early childhood is vital for cognitive, social, and emotional growth. During preschool years, children expand their vocabulary and improve pronunciation, enhancing their communication skills. However, factors such as limited language exposure and socio-economic challenges can impede this development, potentially leading to long-term communication issues. This study explores innovative strategies to boost vocabulary and pronunciation in preschoolers, providing valuable insights for educators, parents, and speech therapists. By emphasizing effective techniques, the research aims to enhance preschool education programs and support children’s linguistic growth, ultimately contributing to their academic success and social adaptability in a diverse world.